Descriptive categories of people according to different age-groups - Roselli, Nestor Daniel (2022)
The most usual descriptors to characterize people are age, sex, physical aspect, and psychological-sociological traits deduced from the appearance. The central hypothesis is that the use of these descriptors varies according to both the age of the group-perceptor and the age of people object of perception. Specifically, the analysis is focus on age as a descriptive category attending the age of the perceptor and the age of the perceived people. Three samples are compared: young people, adults and older adult, who had to describe four photos of people of different ages: little girl, young boy, adult man and elderly woman. First the comparison is between the four photos inside each age-group; then the comparison is between the three age-groups. In all cases coincidences and differences were shown. As expected, age and sex are the most frequent references, but the weight of each one changes according to the age-group and the photos. Also, there are important differences concerning the use of sociological descriptors. Instead, psychological descriptors tend to be more stable. These results highlight the representational differences between age-groups, which is of great importance from the point of view of intergenerational relations.